Conservation Agriculture in a Rice-Wheat Cropping System on an Alluvial Soil of North-Western Indo-Gangetic Plains: Effect on Soil Carbon and Nitrogen Pools - M.c. Meena, T.k. Das and V.k. Singh, Abir Dey, B.s. Dwivedi Ranjan Bhattacharyya, S.p. Datta (Journal of the Indian Society of Soil Science, 2016)
Improving soil organic carbon (SOC) and nitrogen (N) in arable soils is one of the important strategies to enhance soil quality for sustainable crop production and to mitigate climate change. Hence, we investigated the changes in SOC and N under conservation agriculture (CA) in an alluvial soil of the north-western Indo-Gangetic Plains (IGP) after two years of rice (Oryza sativa L.)-wheat (Triticum aestivum L.) rotation. The treatments were: Puddled transplanted rice followed by conventional-till wheat (TPR-CTW), TPR followed by zero-till wheat (TPR-ZTW), Direct-seeded rice followed by ZTW (DSR-ZTW), DSR-ZTW with rice residue retention in ZTW (DSR-ZTW+RR), DSR-ZTW with Sesbania brown manuring (DSR+BM-ZTW), DSR+BM-ZTW+RR, DSR-ZTW with ZT summer mungbean (greengram) (Vigna radiata) as a relay crop and mungbean residues retained on rice fields as in-situ green manuring (MBR+DSR-ZTW-ZTMB) and MBR+DSR-ZTW+RR-ZTMB. Results indicated that plots under CA (MBR+DSR-ZTW+RR-ZTMB) had significantly higher Walkley-Black C, KMnO4-C and very labile SOC compared with TPR-CTW in surface (0-15 cm) soil. Interestingly, addition of residues with mixed C:N ratios (legume and rice residues) failed to register improvement in soil mineral N, owing possibly to greater portioning of N towards soil microbial biomass (SMB) and particulate organic matter (POM) associated pools. Fascinating results could be expected in the present experiment with the passage of time.